2016
DOI: 10.1007/s00221-016-4705-6
|View full text |Cite
|
Sign up to set email alerts
|

Musicians have enhanced audiovisual multisensory binding: experience-dependent effects in the double-flash illusion

Abstract: Musical training is associated with behavioral and neurophysiological enhancements in auditory processing for both musical and nonmusical sounds (e.g., speech). Yet, whether the benefits of musicianship extend beyond enhancements to auditory-specific skills and impact multisensory (e.g., audiovisual) processing has yet to be fully validated. Here, we investigated multisensory integration of auditory and visual information in musicians and nonmusicians using a double-flash illusion, whereby the presentation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
63
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 72 publications
13
63
3
Order By: Relevance
“…It follows, that if the reliability of the auditory 404 dimension of the audiovisual events in our experiment is considered low in some participants 405 and high in others, then they will give more weight to the visual and auditory dimensions, 406 respectively. This is in line with recent evidence that musicians who specialize in the auditory 407 domain are less susceptible to audiovisual illusions (Bidelman, 2016 it was only statistically significant in the right hemisphere. A possible explanation for this 415 discrepancy could be rooted in the fact that larger amplitudes were seen in the right than in 416 VISUAL ENHANCEMENT OF THE MMNm AND AUDITORY SENSITIVITY 21 the left hemisphere.…”
Section: Results 153supporting
confidence: 91%
“…It follows, that if the reliability of the auditory 404 dimension of the audiovisual events in our experiment is considered low in some participants 405 and high in others, then they will give more weight to the visual and auditory dimensions, 406 respectively. This is in line with recent evidence that musicians who specialize in the auditory 407 domain are less susceptible to audiovisual illusions (Bidelman, 2016 it was only statistically significant in the right hemisphere. A possible explanation for this 415 discrepancy could be rooted in the fact that larger amplitudes were seen in the right than in 416 VISUAL ENHANCEMENT OF THE MMNm AND AUDITORY SENSITIVITY 21 the left hemisphere.…”
Section: Results 153supporting
confidence: 91%
“…While these relatively low-level effects have been found to play a role, the current research has shown that higher level factors such as lifelong training can also play a role. While this is the first such experiment to show differences in audiovisual integration capacity, there is previous literature showing similar differences on perception of audiovisual synchrony perception [21], width of temporal binding window [23], McGurk susceptibility [27], and working memory capacity [26].…”
Section: Discussionmentioning
confidence: 61%
“…Another study hypothesized that musicians, compared with non-musicians, would have a significantly enhanced temporal binding window, with greater accuracy on audiovisual integration tasks [23]. When discussing facets of multisensory perception such as the temporal binding window, it is commonly held that a 'wider' window (e.g., binding stimuli that are more disparate in time) is indicative of inferior function.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we compared novel word learning in musicians and nonmusicians by using three concatenated tasks that are dependent upon a variety of perceptual and cognitive functions typically involved in both music and language processing (Dittinger et al, 2016). Based on previous evidence pointing to an optimization of perceptual discrimination (Chobert et al, 2014;Marie et al, 2011), short-term and working memory (George & Coch, 2011;Schulze & Koelsch, 2012), executive functions (Zuk et al, 2014), and audiovisual integration (Bidelman, 2016;Paraskevopoulos, Kraneburg, Herholz, Bamidis, & Pantev, 2015) in musicians, we predicted that the musicians' advantage in word learning would translate into increased EEG-based functional connectivity along the ventral-and dorsal processing streams. Results consistently revealed increased beta coherence in the ventral compared to the dorsal stream during both the "matching-" and "semantic tasks."…”
Section: Discussionmentioning
confidence: 99%